Memmler's the human body in health and disease - Cohen, Barbara J.; Hull, Kerry L. (2019)
"Publisher's Note: Products purchased from 3rd Party sellers are not guaranteed by the Publisher for quality, authenticity, or access to any online entitlements included with the product. Updated in content and pedagogy, this 14th Edition of Memmler's the Human Body in Health and Disease has helped hundreds of thousands of allied health students, including those with little background in science, to master anatomy and physiology. From its pioneering use of phonetic pronunciations to its pedagogically effective skin-to-bone transparencies of the human body, and this edition's "just-in-time" prerequisite content remediation and increased focus on visualization, the new edition continues to set the standard for the one-semester course. This classic text provides beautifully illustrated coverage of the essentials of human anatomy, physiology, and the effects of disease. Throughout the book, anatomical art illustrates concepts with accuracy, simplicity, and elegance; medical case studies enhanced with additional clinical content to demonstrate the relevance of the content to a career in the health professions; and proven pedagogy helps students master the anatomic and medical terminology they will encounter in healthcare settings. To even better support student mastery of key content, the book's online resources are now organized into two sections: text-specific learning tools and interactive study and review. eBook options available. Fast, smart, and convenient, today's eBooks can transform learning. These interactive, fully searchable tools offer 24/7 access on multiple devices, the ability to highlight and share notes, and much more NEW! The latest advances and research in the field are incorporated into every chapter of the book. Key Concepts are now aligned with student resources on thePoint. Casepoints link content to the opening case study. Misconception Alerts point out common student misconceptions, as identified by the PrepU adaptive quizzing program. REVISED! An updated and improved art program brings concepts to life. The Body Visible, a full-body transparency insert, assists students in performing a virtual dissection of the human body from skin down to bone and allows them to test themselves on their understanding of skin, muscles, bones, veins/arteries, etc. Disease in Context boxes provide an introductory case study illustrating a key concept in a particular chapter. Process Diagrams call out the steps of a complex process, such as negative feedback control or maintaining homeostasis and feedback mechanisms. Chapter Checkpoints include brief questions at the end of main sections to reinforce student recall. Phonetic pronunciations of key or difficult terms are spelled out in the narrative directly preceding the terms. Clinical Perspectives boxes focus on relevant diseases and disorders. Hot topics boxes examine current trends and research. Personalized, chapter-by-chapter quizzes powered by PrepU help students learn more and improve their pass rates on exams. Zooming in questions in figure captions allow students to test their understanding of important aspects of the illustration. A Look Back feature highlights previous concepts that will apply to their understanding the current chapter."--Provided by publisher
Organization of the human body -- Chemistry, matter, and life -- Cells and their functions -- Tissues, glands, and membranes -- Disease and disease-producing organisms -- The integumentary system -- The skeletal system: bones and joints -- The muscular system -- The nervous system: the spinal cord and spinal nerves -- The nervous system: the brain and cranial nerves -- The sensory system -- The endocrine system: glands and hormones -- The blood -- The heart and heart disease -- Blood vessels and blood circulation -- The lymphatic system and lymphoid tissue -- Immunity -- The respiratory system -- The digestive system -- Metabolism, nutrition, and body temperature -- The urinary system -- Body fluids -- The male and female reproductive system -- Development and birth -- Heredity and hereditary disease
Includes bibliographical references and index
Includes bibliographical references and index
Keywords: Human physiology; Physiology, Pathological; Human anatomy; Physiological Phenomena; Anatomy; Pathology; Textbooks